Educação integral em tempo integral: as concepções dos docentes de uma escola municipal de ensino fundamental - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The present thesis aims at apprehending teachers conceptions about Integral Integral Education in Integral Time (EITI) in the context of practice in a primary school in the city of Ponta Grossa-PR. In order to help achieve this goal, the following specific objectives were established: delineate the professional profile of the teachers who work in a Public School of Integral Education in Integral Primary Education in the city of Ponta Grossa-PR; to reflect on the teaching practice highlighting EITI conceptions in the context of a Public School of Elementary Education; to present the limits and possibilities of the EITI from the perspective of the teachers who participated in the research. The methodological approach used was the case study with a qualitative data analysis approach. The time period covers the years 1988 to 2018 due to the fact that the first document that has reference on the EITI is the Constitution of 1988, being this the year of departure, until the year of 2018 that the data of the EITI were collected and analyzed. The research universe corresponds to the Municipal School Professor Zilá Bernadete Bach - Infant Education and Elementary Education, of Integral Education in Integral Time, located in the city of Ponta Grossa-PR. The research subjects are the elementary school teachers (1st to 5th year) of this school. The data collection instruments correspond to a questionnaire, prepared by the researcher, also analyzed the federal, state, municipal documents and the school itself. The collected data were analyzed from a qualitative and quantitative approach, through graphs and categories of analysis. The theoretical reference used in the analysis consists mainly of the following authors from the EITI area: Ana Maria Cavaliere (1996, 2004, 2006; Jaqueline Moll (2011; 2012); and Ligia Coelho (1996; 2004; 2009). The analysis of the teachers conception about EITI, stated in the questionnaire, allowed the reflection about the relationship between theory and practice in the context of acting in a municipal school of EITI.
Keywords: Educação integral em tempo integral; Prática docente; Ensino Fundamental; Escola Pública; Integral education in integral time; Teaching practice; Elementary School; Public school; CNPQ::CIENCIAS HUMANAS::EDUCACAO